(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article explains and interprets geological terminology and concepts. The significance of developing new terms and lexemes for the construction of terminology systems related to geological branches was demonstrated. Some scientists’ viewpoints were expressed in this regard